Analysis of Intervention Effects of Prototyping Utilizing UI Stencils in Elementary School Students - Toshiharu Igarashi; Yu Chen (MDPI AG, 2024)
This study examines the impact of using stencils in paper prototyping on work time, subjective burden, and idea generation among Japanese sixth-grade students, focusing on the role of personality traits, specifically openness. Two groups were involved: Group 1 used stencils after a lecture, and Group 2 worked freehand without prior instruction. Results showed no significant difference in work time; however, a reduction in subjective burden was noted in the stencil group. While no significant correlation was found between openness and the number of stencil icons used, children with higher openness scores engaged more intensively, suggesting that stencils influence the quality and depth of engagement. The findings highlight the importance of tailored educational approaches to enhance learning outcomes.